Indoleamine 2, 3-Dioxygenase Promotes Aryl Hydrocarbon Receptor-Dependent Differentiation Of Regulatory B Cells in Lung Cancer - Tousif, Sultan; Wang, Yong; Jackson, Joshua; Hough, Kenneth P.; Strenkowski, John G.; Athar, Mohammad; Thannickal, Victor J.; McCusker, Robert H.; Ponnazhagan, Selvarangan; Deshane, Jessy S. (Frontiers in Immunology, 2021)
Regulatory B cells (Breg) are IL-10 producing subsets of B cells that contribute to immunosuppression in the tumor microenvironment (TME). Breg are elevated in patients with lung cancer; however, the mechanisms underlying Breg development and their function in lung cancer have not been adequately elucidated. Herein, we report a novel role for Indoleamine 2, 3- dioxygenase (IDO), a metabolic enzyme that degrades tryptophan (Trp) and the Trp metabolite L-kynurenine (L-Kyn) in the regulation of Breg differentiation in the lung TME. Using a syngeneic mouse model of lung cancer, we report that Breg frequencies significantly increased during tumor progression in the lung TME and secondary lymphoid organs, while Breg were reduced in tumor-bearing IDO deficient mice (IDO-/-). Trp metabolite L-Kyn promoted Breg differentiation in-vitro in an aryl hydrocarbon receptor (AhR), toll-like receptor-4-myeloid differentiation primary response 88, (TLR4-MyD88) dependent manner. Importantly, using mouse models with conditional deletion of IDO in myeloid-lineage cells, we identified a significant role for immunosuppressive myeloid-derived suppressor cell (MDSC)-associated IDO in modulating in-vivo and ex-vivo differentiation of Breg. Our studies thus identify Trp metabolism as a therapeutic target to modulate regulatory B cell function during lung cancer progression